1998
DOI: 10.1002/(sici)1099-081x(199807)19:5<291::aid-bdd106>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of moderate and chronic exercise training on the pharmacokinetics of procainamide and N-acetylprocainamide

Abstract: The effect of moderate and prolonged exercise on the disposition and metabolism of drugs has not been extensively examined. The present study examined the effect of exercise training on the pharmacokinetics of procainamide and its active metabolite, N‐acetylprocainamide. Male Sprague Dawley rats were randomly assigned to three testing groups: (1) sedentary, (2) 4 weeks of exercise training and (3) 8 weeks of exercise training. Treadmill speed and exercise duration were gradually increased, reaching a final rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The serum pharmacokinetics of NACPA following intravenous administration are characterized by rapid absorption, distribution and elimination, which have been observed for many other benzamides [16][17][18]. Drugs with these features are not readily accumulated in the body and have less toxic effects when administered repeatedly.…”
Section: Discussionmentioning
confidence: 97%
“…The serum pharmacokinetics of NACPA following intravenous administration are characterized by rapid absorption, distribution and elimination, which have been observed for many other benzamides [16][17][18]. Drugs with these features are not readily accumulated in the body and have less toxic effects when administered repeatedly.…”
Section: Discussionmentioning
confidence: 97%
“…Given exercise training, there can still be different pharmacokinetic effects. Previous studies indicated that exercise training reduced the amount of N-acetylprocainamide concentration (17). Kim et al indicated no difference in azosemide absorption in rats after treadmill running (18).…”
Section: Introductionmentioning
confidence: 99%